2018
DOI: 10.1007/s00246-018-1876-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Placenta in the Newborn with Congenital Heart Disease: Distinctions Based on Type of Cardiac Malformation

Abstract: The placenta is a complex organ that influences prenatal growth and development, and through fetal programming impacts postnatal health and well-being lifelong. Little information exists on placental pathology in the presence of congenital heart disease (CHD). Our objective is to characterize the placenta in CHD and investigate for distinctions based on type of malformation present. Placental pathology from singleton neonates prenatally diagnosed and delivered at > 37 weeks gestation was analyzed. Placental fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 31 publications
(38 reference statements)
5
89
1
3
Order By: Relevance
“…Recent studies support that both growth restriction (17–18%) and placenta‐related complications, such as pre‐eclampsia, occur more frequently in CHD cases. However, as previous studies reporting on HC in CHD did not look at birth weight, growth trajectories or additional genetic pathology, their findings may, in our opinion, be explained by additional pathology.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies support that both growth restriction (17–18%) and placenta‐related complications, such as pre‐eclampsia, occur more frequently in CHD cases. However, as previous studies reporting on HC in CHD did not look at birth weight, growth trajectories or additional genetic pathology, their findings may, in our opinion, be explained by additional pathology.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies even reported morphological changes in brain structures in CHD fetuses using fetal MRI or three-dimensional ultrasound, which was correlated with severity of CHD [8,26,27]. Furthermore, a link between placental abnormalities and type of CHD has been reported by Rychik et al, who characterized the placenta in CHD and looked for distinctions based on type of malformation [28]. They found a high percentage of placental abnormalities in CHD newborns, including chorangiosis (18 %), hypomature villi (15 %), thrombosis (41 %) and infarction (17 %).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal placentation is seen in both fetuses and gravidas with CHD. Rychik et al in a single‐center cohort study found that fetuses with complex CHD had significant placental pathology, including low placental‐to‐birth weight ratio, abnormal chorangiosis, hypomature villi, thrombosis, and infarction (Rychik et al, ). Conversely, women with CHD are more likely to have abnormal uteroplacental blood flow examined by Doppler ultrasound suggestive of abnormal placentation (Balci et al, ; Pieper et al, ).…”
Section: Association Of Human Chd With Early Onset Placental Insufficmentioning
confidence: 99%